FUTURE POPULATION PREDICTION 2050 OF BANTEN PROVINCE, JAKARTA, JAWA BARAT, JAWA TENGAH, DAERAH ISTIMEWA YOGJAKARTA, JAWA TIMUR, USING WORLDPOP DATA WITH GOOGLE EARTH ENGINE - Rakuasa, Heinrich; Lasaiba, Mohammad Amin (Journal of Data Analytics, Information, and Computer Science, 2024)
This study uses WorldPop data and the Earth Engine platform to predict population in Banten, Jakarta, West Java, Central Java, Special Region of Yogyakarta and East Java Provinces. Through high-resolution grid-based analysis, the study identifies patterns of population growth that are not visible with traditional, more aggregated data. Prediction results show significant population increases from 2020 to 2023, with Jakarta and West Java experiencing the most notable growth. Predictions for 2050 show significant population increases in all provinces, with Jakarta and West Java being the provinces with the highest populations. The implications of these population dynamics for infrastructure planning and public policy are critical to anticipate rapid population growth. This information can be used for more effective resource allocation, targeted infrastructure planning, and improved public welfare. Thus, this research is expected to make a significant contribution to regional planning and sustainable development, as well as in facing future demographic challenges.